Thermoelectric device for treatment of skin diseases - Anatychuk, L.I.; Denysenko, O.I.; Kobylianskyi, R.R.; Stepanenko, V.I.; Svyryd, S.G.; Stepanenko, R.L.; Perepichka, M.P. (Journal of Thermoelectricity, 2019)
The paper presents the results of development of a thermoelectric device for treatment of skin diseases. The developed device has an extended range of operating temperatures (-50 ÷ 0) °С and visual control of the temperature of cooling work tools during therapeutic procedures. The design features of the device, its technical characteristics and the results of testing in clinical practice are given. Bibl. 44, Fig. 6, Tabl. 1.